Do Rebranding and Relocation Affect Marketing Strategy in Culinary Business; A Lesson from "Kedai Lobster" - Nada Maharani Wiradarya; Idqan Fahmi (Business Review and Case Studies, 2020)
Since Kedai Lobster did a rebranding and relocation, sales has been decreasing. Are there any relation between rebranding and relocation with sales decrease and how to increase the sales volume is the problem that will be investigated. This research was conducted with the aim to: analyse respondents assessment of the importance level of restaurant marketing mix attributes in general, analyse the level of performance of the Kedai Lobster marketing mix and formulate marketing strategy for Kedai Lobster. This research will be analysed using descriptive analysis and Importance Performance Analysis (IPA). Based on the results of the IPA diagram, strategies that can be formulated are adjusting the product price with the portion, stocking the ingredients, creating Kedai Lobster neon box, increasing the quality and intensity of social media promotions, replacing the restaurant lighting, adding air conditioners, and providing music (non live). Keywords: Marketing mix, IPA, rebranding, relocation, marketing strategy